A case report of tumor-associated liver injury alleviated with antineoplastic drug - Yang, ZiRu; Cao, Lixia; Kuai, Wentao; Yao, Shengjuan; Li, Shuang; Xu, Liang (Frontiers in Oncology, 2025)
Tumors are the major diseases that threaten people’s health and life at present. Liver injury often happens in patients with cancer, and which mostly attribute to application of anti-cancer drugs. However, some cases caused by the infiltration and destruction of metastatic cancer, and anti-tumor drugs play a key role in restoring liver function instead of inducing drug induced liver injury (DILI). This article reports a case of tumor-associated Liver Injury (TALI) who suffered HER2-negative metastatic breast cancer with liver metastasis, but her liver function was recovery after treatment with Alpelisib, an anti-tumor drug, as meanwhile as achieving anti-tumor. Through this case we aims to emphasize to differentiate the causes of TALI and make the treatment strategies accordingly.